Dopamine modulates synaptic plasticity in dendrites of rat and human dentate granule cells - Hamilton, Trevor J. (National Academy of Sciences, 2010)
The mechanisms underlying memory formation in the hippocampal network remain a major unanswered aspect of neuroscience. Although high-frequency activity appears essential for plasticity, salience for memory formation is also provided by activity in ventral tegmental area (VTA) dopamine projections. Here, we report that activation of dopamine D1 receptors in dentate granule cells (DGCs) can preferentially increase dendritic excitability to both high-frequency afferent activity and high-frequency trains of backpropagating action potentials. Using whole-cell patch clamp recordings, calcium imaging, and neuropeptide Y to inhibit postsynaptic calcium influx, we found that activation of dendritic voltage-dependent calcium channels (VDCCs) is essential for dopamine-induced long-term potentiation (LTP), both in rat and human dentate gyrus (DG). Moreover, we demonstrate previously unreported spike-timing–dependent plasticity in the human hippocampus. These results suggest that when dopamine is released in the dentate gyrus with concurrent high-frequency activity there is an increased probability that synapses will be strengthened and reward-associated spatial memories will be formed.